Mechanical Engineering Students' Perceptions and Experiences with Team-Based Project Learning: a Comprehensive Investigation - Hendri Sulistyo; Agus Solehudin; Mumu Komaro (Universitas Sultan Ageng Tirtayasa, 2026)
Team-Based Project (TBP) learning has gained prominence in engineering education as a means to develop both technical competencies and professional skills through collaborative engagement. Despite extensive documentation of TBP outcomes, limited research has explored the qualitatively different ways in which students understand and experience TBP, particularly within the distinct context of mechanical engineering education programs that integrate technical and pedagogical preparation. This study employs a phenomenographic research design to investigate mechanical engineering education students' qualitatively different ways of experiencing TBP. Data were collected through semi-structured interviews with 63 students at various academic stages across two universities in Indonesia. Analysis followed phenomenographic principles, identifying categories of description that capture qualitative variation in students' understanding, rather than reporting frequency distributions. Findings reveal four qualitatively distinct categories of description: (1) TBP as task completion, (2) TBP as collaborative skill-building, (3) TBP as professional preparation, and (4) TBP as transformative learning. These categories form an outcome space in which more sophisticated conceptions encompass awareness of collaborative processes, professional relevance, and critical reflection. Persistent structural challenges particularly inequitable workload distribution and coordination difficulties feature differently across categories. The study contributes context-specific insights into how TBP is understood in a technically and pedagogically hybrid engineering program, with implications for curriculum design, team formation, and instructor support strategies.